A Sex-Specific Comparative Analysis of Oxidative Stress Biomarkers Predicting the Risk of Cardiovascular Events and All-Cause Mortality in the General Population: A Prospective Cohort Study - Martin F. Bourgonje; Amaal E. Abdulle; Lyanne M. Kieneker; Sacha la Bastide-van Gemert; Stephan J. L. Bakker; Ron T. Gansevoort; Sanne J. Gordijn; Harry van Goor; Arno R. Bourgonje (MDPI AG, 2023)
Oxidative stress plays a pivotal role in cardiovascular (CV) disease, but current biomarkers used to predict CV events are still insufficient. In this study, we comparatively assessed the utility of redox-related biomarkers in predicting the risk of CV events and all-cause mortality in male and female subjects from the general population. Subjects (n = 5955) of the Prevention of REnal and Vascular ENd-stage Disease (PREVEND) population-based cohort study were included. Blood homocysteine, gamma-GT, HDL cholesterol, bilirubin and protein-adjusted free thiol (R-SH, sulfhydryl groups) levels were quantified at baseline and were prospectively analyzed in association with the risk of CV events and all-cause mortality. After adjustment for potentially confounding factors, protein-adjusted R-SH and homocysteine levels were significantly associated with the risk of CV events in men (HR 0.63 [0.40-0.99], p = 0.045 and HR 1.58 [1.20-2.08], p = 0.001, respectively). Protein-adjusted R-SH and HDL cholesterol levels were significantly associated with the risk of all-cause mortality in men (HR 0.52 [0.32-0.85], p = 0.009 and HR 0.90 [0.85-0.94], p < 0.001, respectively), while the same was observed for bilirubin and homocysteine levels in women (HR 0.68 [0.48-0.98], p = 0.040 and HR 2.30 [1.14-3.76], p < 0.001, respectively). Lower levels of protein-adjusted R-SH were robustly associated with an increased risk of CV events and all-cause mortality in men. Our results highlight the value of R-SH levels in cardiovascular risk assessment and their potential significance as being amenable to therapeutic intervention, while reaffirming the importance of other oxidative stress-related biomarkers, such as homocysteine, HDL cholesterol and bilirubin.